Impact of liberalization on the Singapore insurance industry : types of strategic combinations that may arise. - Ng, Mei Hui. (2008)
The MAS seeks to open up the insurance sector of Singapore to more foreign competition, in line with its aim of making Singapore the insurance hub of Asia by year 2003. This project thus aims to examine the impact of such liberalisation on the local insurance sector as well as discuss the forms of strategic combinations that may arise.